International, European and Romanian developments related to the dairy cows: Livestock and production obtained - Ioan-Niculae Alecu; Caroly Nagy; Gyorgy Szabo; Irina Angelescu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 7th Edition of the International Symposium, November 2016, Bucharest, 2016)
Considering the population growth and the need to ensure food security, and also the fact that milk represents one of the basic foods in the diet of children and of adults, this paper seeks to obtain an image that is as accurate as possible of the evolution of dairy cow sector, at the global and European level and also in Romania. By using as working method the direct observation without intervention and by consulting the specialized bibliographical references, we have tried to select the most representative statistical data allowing us a proper analysis of the development of dairy cow sector. The analysis of the development of this sector at the international and European level indicated that the results obtained are decisively influenced by the production potential of the biological material and by the development of the exploitation technologies. Over time, the evolution of livestock was different, according to the development level of countries located in different geographical areas. While in areas such as North America and Europe, a decrease of livestock was noticed, at the same time a s a significant increase of production, in Africa and Asia, the increase of milk production was almost exclusively accomplished by increasing the cattle herd. In Romania, since 1989, the dairy cow sector has been undergoing a strengthening and development process, and the Ministry of Agriculture and Rural Development, by the National Strategy for the Development of the Livestock Sector establishes clear objectives and priorities for its support. The analysis performed allows us to consider that, at least for Romania, the dairy cow sector is yet an inadequately capitalized opportunity that could place our country as a front-runner on the European market.
Keywords: 330; dairy cows; livestock evolution; milk production; modern technologies; biologic material